Sosialisasi Program Seksi Ketentraman Dan Ketertiban Kepada Masyarakat Di Kecamatan Lubuk Pakam Kabupaten Deli Serdang Untuk Menunjang Program Pemerintah Daerah - Evi Yunita Kurniaty; Indra Muda; Bebby Masitho Batubara; Bahrum Jamil; Agung Suharyanto (Pelita Masyarakat, 2021)
Community service activities are one of the activities that aim to assist the government in realizing a stable condition of peace and order in society that will encourage the creation of national stability which will ensure the smooth running of governance and the implementation of national development. The problems raised in this service are: (1) How is the existence of the Peace and Order Section in supporting local government programs in the Lubuk Pakam District, Deli Serdang Regency, (2) What efforts are made by the Peace and Order Section in carrying out their duties? the main tasks and functions, (3) What are the obstacles and obstacles faced by the Section for Peace and Order and how to overcome them. The results of this service show that the main tasks and functions of the Section for Peace and Order play an important role in assisting the main tasks of the Camat and Regional Heads ( Regent) in enforcing and implementing local government programs in the field of public peace and order at the sub-district level. One of them is to carry out routine patrol activities from morning, afternoon, to evening alternately. The efforts made and the obstacles faced and how to overcome them are divided into several fields, namely: the field of institutions, the field of networking, the field of counseling, the field of operations, the field of action, and ending with the field of routine anticipation.